Assessment of right ventricular remodeling in chronic thromboembolic pulmonary hypertension by 2D-speckle tracking echocardiography: A comparison with cardiac magnetic resonance - Wang, Yeqing; Guo, Dichen; Liu, Mingxi; Zhang, Xinyuan; Hu, Huimin; Yang, Hao; Yang, Yuanhua; Lv, Xiuzhang; Li, Yidan; Guo, Xiaojuan (Frontiers in Cardiovascular Medicine, 2022)
Background: Right heart remodeling occurs in a substantial proportion of patients with chronic thromboembolic pulmonary hypertension (CTEPH) and is closely related to the prognosis of patients. Two-dimensional speckle-tracking echocardiography (2D-STE) can be used to evaluate myocardial deformation under physiological and pathological conditions. The purpose of this study was to assess the feasibility of 2D-STE for evaluating right ventricular (RV) remodeling in CTEPH patients. Methods: This retrospective study included 21 CTEPH patients who underwent transthoracic echocardiography (TTE) and cardiac magnetic resonance (CMR). Data for the following parameters that can reflect RV function were collected: tricuspid annular plane systolic excursion (TAPSE), fractional area change (FAC), right ventricular index of myocardial performance (RIMP), peak systolic velocity of tricuspid annulus (S'), and CMR-right ventricular ejection fraction (CMR-RVEF). The following strain parameters were calculated using post-processing software: STE-RV global longitudinal strain (STE-RVGLS), STE-RV free wall longitudinal strain (STE-RVFWLS), and CMR-RVGLS. Results: As CMR-RVEF deteriorated, RV remodeling in CTEPH patients became more apparent and was mainly characterized by significant enlargement of the RV, weakening of myocardial deformation, and a decrease in RV contractility (RV area, STE-RVFWLS, STE-RVGLS: mild vs severe and moderate vs severe, p<0.05; CMR-RVGLS: mild vs severe, p<0.05; TAPSE: moderate vs severe, p<0.05). Moreover, the Pearson correlation coefficient for correlation with CMR-derived RVEF was stronger for RVFWLS than CMR-GLS (r value: 0.70 vs 0.68), and the strain values measured by 2D-STE showed weak correlation with right heart catheterization data. Bland-Altman analysis showed good agreement between 2D-STE and CMR-feature tracking (FT) for RVGLS (bias= –0.96; 95% limit of agreement from –8.42 to 6.49). Conclusions: For measurement of RVGLS, 2D-STE is similarly feasible to CMR-FT and could sensitively identify right heart remodeling.